2008
DOI: 10.1021/es801480u
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Photocatalytic Oxidation Mechanism of As(III)

Abstract: There has been a controversy over the TiO2 photocatalytic oxidation (PCO) mechanism of As(III) for the last several years. The key argument has been whether superoxide (HO2*/O2(-)*) is the main oxidant of As(III) in the UV/TiO2 system. Previously we and other groups have refuted the claim that superoxide plays the main role in the TiO2 PCO of As(III). Nevertheless, thereafter, the superoxide-mediated As(III) oxidation mechanism has been repeatedly claimed, making it difficult to draw a clear conclusion regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 46 publications
4
53
0
Order By: Relevance
“…The role of h vb + was first examined by adding formic acid (FA) to remove it selectively. [24] In the presence of only 2 mm of FA, which was 10 % of the BA concentration, the abundance of 16 O (from 16 O 2 ) in the hydroxylated product increased remarkably (Table 2, . In addition, most of the earlier studies seemed to indicate that the hydroxylation of aromatic compounds is directly related to h vb + or COH generated from it.…”
mentioning
confidence: 97%
“…The role of h vb + was first examined by adding formic acid (FA) to remove it selectively. [24] In the presence of only 2 mm of FA, which was 10 % of the BA concentration, the abundance of 16 O (from 16 O 2 ) in the hydroxylated product increased remarkably (Table 2, . In addition, most of the earlier studies seemed to indicate that the hydroxylation of aromatic compounds is directly related to h vb + or COH generated from it.…”
mentioning
confidence: 97%
“…Based on transient absorption decay as a function of As +3 concentration these workers concluded that adsorbed hydroxyl radical/trapped holes play a central role in the photocatalytic oxidation. Most recently, Yoon et al (2009) have provided a conclusive evidence to support the opinion that hydroxyl radical and valence band hole are the main oxidants in the photocatalytic oxidation of As +3 over TiO 2 . These workers investigated the correlation between As +3 oxidation and superoxide by measuring both As +5 and H 2 O 2 simultaneously.…”
Section: Photocatalytic Oxidation Of Inorganic Cationsmentioning
confidence: 86%
“…Advanced oxidation processes (AOPs) are impressed as highly competitive technologies for elimination of a wide variety of recalcitrant organics resistant to conventional approaches [3][4][5][6][7][8][9][10][11]. Among all AOPs, TiO 2 photocatalysis is capable of converting photon energy into chemical energy, and proves to be a green, eco-friendly and efficient tool for wastewater treatment and water purification [8,9,12].…”
Section: Introductionmentioning
confidence: 99%